Perceptual expertise in handball - Schorer, J.; Panten, J.; Neugebauer, J.; Loffing, F. (Handball Sports Medicine, 2018)
In this chapter, we review and discuss the empirical evidence on perceptual expertise available from the handball literature so far that relates to the four groups of actors—goalkeepers, field players, coaches and referees. As will be clear from the following sections, considerable effort has been invested in examining and understanding goalkeepers` perceptual-cognitive skills; however, comparatively less is known about these skills in the other three groups. In this regard, we hope this chapter encourages intensification of efforts in investigating perceptual-cognitive skills as one factor deemed relevant, among others, to different actors` performances in handball.